Practical Java Game Programming - Clingman, Dustin
Java is gaining more and more acceptance in the game development community, and with good commercial-quality Java games on the market, it will become a definitive choice. Practical Java Game Programming identifies the technological path developers need to take to make this happen. It explores and illustrates cutting-edge Java game programming concepts and techniques through specific explanations from existing Java game projects, with fully executable example code. Intended for both Java programmers new to game development, and for game programmers interested in Java, the book offers usage patterns that leverage Java's strengths and points out weaknesses to avoid. It teaches Java programmers how to deliver outstanding games and details the specific issues in Java to make game development straightforward and efficient. Java has always provided a powerful platform on which to develop interactive content, and with the addition of the Java Technology Groupãưs gaming APIs, Java becomes a third-party platform choice and delivery model for game developers. Each chapter includes working code examples that can stand alone for easy implementation into one's own projects, or be used toward the creation of a fully functional demo game. This allows beginning programmers to follow the topics step-by-step, and more experienced programmers to use specific areas of interest. Although this book is centered on Java and the platform technologies, its message is for developers to maintain a wide view regarding new technologies, as well as to keep creative ingenuity intact while implementing games on the Java platform